Cognitive Development of Children Aged 4-7 Years During The Covid-19 Pandemic - Anita Oktaviana; Indah Srianggita (JOYCED: Journal of Early Childhood Education, 2021)
Cognitive development is one aspect of child development that is very important to get intervention during the COVID-19 pandemic, Cognitive development is a development that is closely related to thinking skills, such as reasoning, memory, and the ability to solve practical problems. The cognitive mindset of early childhood is very much different from people who are teenagers and adults or even children who are in middle school and above. Elementary school age children have limitations in thinking about abstract things, cognitive development has a correlation with other developments and will have an impact especially on children's academic abilities. The purpose of this paper is to examine how the cognitive development of early childhood during the covid-19 pandemic and what strategies are carried out by parents in developing cognitive development of early childhood during the covid-19 pandemic? Based on the formulation of the problem above, the data analysis technique used in this study is an interactive model of data analysis in analysing the data carried out in three ways, namely data reduction activities, data presentation and also data conclusions. as well as parents. These results and discussions describe various issues related to cognitive development problems such as several barriers to children's activities and activities that have an impact on children's cognitive during the COVID-19 pandemic in Pangkalan Kuras District, Pelalawan Regency, Riau Province. In conclusion, this study aims to describe the cognitive development of early childhood during the COVID-19 pandemic and provide views regarding several activities that can be internalized to stimulate children's cognitive development.